2019
DOI: 10.1016/j.jadohealth.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Developing Experimental Vignettes to Identify Gender Norms Associated With Transactional Sex for Adolescent Girls and Young Women in Central Uganda

Abstract: PurposeTransactional sex or informal sexual exchange relationships increase adolescent girls' and young women's (AGYW) HIV and pregnancy risk in sub-Saharan Africa. These relationships are grounded in the shared expectation that men should provide financial support to their partners. We built a vignette experiment to assess whether gender norms influenced by expectations of provision help to explain how transactional sex increases AGYW's sexual and reproductive health risks.MethodsWe used mixed methods to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 42 publications
5
22
0
Order By: Relevance
“…That reported early engagement in transactional sex is associated with more recent sexual risk behaviors (i.e. no or infrequent condom use and multiple sex partners in the past 12 months) may be in part explained by gender norms and beliefs that underlie transactional sex [ 46 ]. Transactional sex stems from broader gender expectations of relationships within patriarchal societies–that men are expected to provide for their partners and women, in turn, to provide sexual services [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That reported early engagement in transactional sex is associated with more recent sexual risk behaviors (i.e. no or infrequent condom use and multiple sex partners in the past 12 months) may be in part explained by gender norms and beliefs that underlie transactional sex [ 46 ]. Transactional sex stems from broader gender expectations of relationships within patriarchal societies–that men are expected to provide for their partners and women, in turn, to provide sexual services [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study found evidence for a higher social acceptance of men’s control over sexual decision-making power in relationships when they provide more material support. The study also found evidence for increased peer acceptance of young women taking on an additional sexual partner if their primary partner is perceived as not providing enough material support [ 27 ]. While the Uganda VACS did not have measures to allow replication of this study, this pilot study provides insight that women who engage in relationships motivated by male provision may be more likely to adhere to expectations that men should control sexual decision-making, including whether or not to use condoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 56 This could be particularly valuable given strong normative expectations of male provision, where AGYW describe strong expectations for their partner to provide for them, even when they have access to other resources. 57 Another important avenue could be to recruit existing norms around parenting and parents’ perceived obligations to safeguard their daughters. This could build on parents’ existing efforts to ascertain the source of their daughters’ resources while also prompting recognition of the impact of expecting AGYW to contribute economically to the household in the absence of any income-generation opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Using multiple regression analysis, they find that, net of several sociodemographic variables, five out of six of these perceived norms variables are significantly associated with perceived agency. Another contribution describes the development of new measures of social norms related to transactional sex among adolescent and young adult women in Uganda [17] . Rather than focusing on social norms regarding transactional sex itself, however, this work uses experimental vignettes to measure social norms regarding men's obligation to provide material support to women and the sexual and other obligations that this support generates for young women.…”
mentioning
confidence: 99%